Efektivitas Model Pembelajaran SETS Terhadap Kemampuan Berpikir Kritis pada Siswa Berkemampuan Rendah (Single Subject Research) - Inayah Adini Putri; Rohmat Widiyanto; Marzuki Mahmud (Elementar : Jurnal Pendidikan Dasar, 2021)
This study aims to analyze students' critical thinking skills carried out at SD Kedoya Utara 04 in the second semester of the 2019/2020 school year. The research method used was Single Subject Research with A-B-A design. The subjects of this study were 3 grade V students not fast enough to understand in learning. The instrument used in the study was the description test. The results of this study indicate that in the intervention conditions all subjects have the ability to think critically. Critical thinking skills of subjects 1 and 3 at baseline-2 (A2) conditions are higher than baseline-1 (A1) conditions, have the same critical thinking skills. While the critical thinking ability of subject 2 in the baseline-1 (A1) conditions is slightly lower than subjects 1 and 2. In general, the conclusion of this study is that the provision of the SETS learning model consists of preliminary stages, concept formation, Concept application, conceptualization and assessment can improve students' critical thinking skills in identifying indicators, interpretation, analysis, inference, and explanation.Keywords: Single Subject Research, Not Fast Enough to Understand in Learning, Critical Thinking Ability, Model SETS Learning